Bedside Nursing Handover: Patient’s Perspective - Ahmad Rifai; Alfid Tri Afandi; Asmaul Hasanah (Faculty of Nursing, Universitas Jember, 2019)
Bedside handover is one of nursing care activities which involve patient during nurse-patient interaction a side of patient’s bed between change shift. Patient may inquire all they want to know about their health condition, complaining and request for nursing care. However, the bedside handover often ineffectively run when a group of nurse hand in the nursing care plan for the following nurses shift. This study aimed to describe bedside handover activities based on patient’s perspective in inpatient ward at one military hospital at Jember. This research used a quantitative approach with a descriptive survey design. There were 100 respondents recruited in this study using purposive sampling technique with criteria the patients had received nursing care at least two days in the inpatient ward. Data were collected using bedside report item survey questionnaire to measure bedside handover based on patient perception. The results showed the median of bedside handover was 33 (min-max = 10-40), indicated that the bedside handover from patient’s point of view was in good category. Basically, the nurses have implemented the bedside handover, however there are problems occurred during its’ implementation such as, high burden of nurse’s work, limited time, lack of understanding and awareness regarding bedside handover. Patients have right to receive holistic nursing care, and it is the responsibility of nurses to provide excellent service including the action of bedside handover. Nursing manager should evaluate and supervise the bedside handover for all nurses routinely.